Tracing the undercurrents: a scoping review of the lifestyle drift concept - Halsall, Tanya; Orpana, Heather; Jan, Misha (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Lifestyle drift refers to the tendency for health interventions that are initially intended to address upstream social determinants of health to shift focus toward downstream efforts targeting individual behaviours. Although increasingly cited in the literature, as far as we are aware, no scoping or systematic reviews that examine the concept of lifestyle drift exist. The objective of this scoping review is to summarize the existing literature on lifestyle drift, describe how it is defined in the literature, the causes or mechanisms of influence that lead to lifestyle drift and ways to address it. Methods A comprehensive search strategy was developed with guidance from a librarian and seven databases were searched. Title and abstract and full text screening was conducted in Covidence according to inclusion and exclusion criteria. Included documents were imported into NVivo, and data from articles were analysed using a thematic analysis approach. Results We identified 318 articles and 32 met the inclusion criteria with lifestyle drift as a focus or major theme. Definitions of lifestyle drift shared some common elements along with variability of concepts. Neoliberalism and the biomedical model were frequently identified as drivers of lifestyle drift across articles. While many strategies to counteract lifestyle drift were proposed, applying a health in all policies approach, and participation from priority populations were the most common strategies suggested. Conclusion While lifestyle drift is a recognized concern in public health, health promotion and chronic disease prevention, there remains a need for more empirical research on lifestyle drift, including mechanisms and mitigation. Strengthening understanding of how to identify, prevent, and address lifestyle drift may enhance the effectiveness of upstream interventions aimed at reducing health inequities.